Kepemimpinan transformasional, employee engagement, lingkungan kerja dan kepuasan kerja pada karyawan - Septiara Sari; Umi Farida; Titis Purwaningrum (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
Job satisfaction is an essential factor in the success of company goals. A company is also required to be able to manage the human resources in the company properly through efforts to pay attention to the leadership style adopted, maintain employee involvement with the company, and the working environment conditions around the employee so that employee work results can be achieved. As expected, in the end, employees are satisfied with their current job. Furthermore, company goals can be achieved. The study aims to determine the impact of transformational leadership, employee engagement, and the work environment on employee job satisfaction. Using this type of quantitative research with a questionnaire of 50 respondents, The analytical methods used are multiple linear regression. The results show that transformational leadership has a significant positive effect on job satisfaction, employee engagement has a significant positive effect on job satisfaction, and the work environment has a significant positive effect on job satisfaction. This research provides benefits to increase job satisfaction for employees.